Exploring the Potential of Corynebacterium glutamicum to Produce the Compatible Solute Mannosylglycerate - Schwentner, Andreas; Neugebauer, Heiko; Weinmann, Serin; Santos, Helena; Eikmanns, Bernhard J. (Frontiers in Bioengineering and Biotechnology, 2021)
The compatible solute mannosylglycerate (MG) has exceptional properties in terms of protein stabilization and protection under salt, heat, and freeze-drying stresses as well as against protein aggregation. Due to these characteristics MG possesses large potential for clinical and biotechnological applications. To achieve efficient MG production, Corynebacterium glutamicum was equipped with a bifunctional MG synthase (encoded by mgsD and catalyzing the condensation of 3 phosphoglycerate and GDP mannose to MG) from Dehalococcoides mccartyi. The resulting strain C. glutamicum (pEKEx3 mgsD) intracellularly accumulated about 111 mM MG (60 ± 9 mg gCDW-1) with 2 % glucose as carbon source. To enable efficient mannose metabolization, the native manA gene, encoding mannose 6 phosphate isomerase, was overexpressed. Combined overexpression of manA and mgsD from two plasmids in C. glutamicum resulted in intracellular MG accumulation of up to ca. 329 mM [corresponding to 177 mg g cell dry weight (CDW) 1] with glucose, 314 mM (168 mg gCDW 1) with glucose plus mannose, and 328 mM (176 mg gCDW 1) with mannose as carbon source(s), respectively. The product was successfully extracted from cells by using a cold water shock, resulting in up to 5.5 mM MG (1.48 g L 1) in supernatants. The two-plasmid-system was improved by integrating the mgsD gene into the manA-bearing plasmid and the resulting strain showed comparable production but faster growth. Repeated cycles of growth/production and extraction of MG in a bacterial milking-like experiment showed that cells could be recycled, which led to a cumulative MG production of 19.9 mM (5.34 g L-1). The results show that the newly constructed C. glutamicum strain produces MG from glucose and mannose and that a cold water shock enables extraction of MG from the cytosol into the medium.